2006
DOI: 10.1681/asn.2005010102
|View full text |Cite
|
Sign up to set email alerts
|

A Pathophysiologic Role for T Lymphocytes in Murine Acute Cisplatin Nephrotoxicity

Abstract: Recent evidence supports a role for an inflammatory pathogenesis of cisplatin nephrotoxicity, but immune cell-mediated mechanisms in this disease are still largely unknown. The role for T lymphocytes on cisplatin-induced acute kidney injury was examined with C57BL/6 T cell-deficient (nu/nu) mice and CD4-or CD8-deficient mice and their wild-type (WT) littermates. All mice received a single dose of cisplatin at 40 mg/kg (intraperitoneally) and were followed up for 72 h. At 72 h after cisplatin administration, T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
156
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 31 publications
12
156
1
1
Order By: Relevance
“…After intraperitoneal (ip) cisplatin injection, we noted infiltrating eGFP + T cells scattered throughout the renal parenchyma (Figure 1B) peaking at 12 hours, consistent with previous findings by Liu et al 11 We then tested whether abrogating AT 1 receptor signals selectively within T lymphocytes influences the development of cisplatin-induced AKI. Wildtype (WT) mice and mice genetically deficient of the dominant murine AT 1 receptor isoform (AT 1A ) solely within T cells (TKO; Supplemental Figure 1) had similar levels of BUN and serum creatinine (sCr) after saline treatment, indicating that the T cell AT 1 receptor does not affect baseline renal function ( Figure 1, C and D).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…After intraperitoneal (ip) cisplatin injection, we noted infiltrating eGFP + T cells scattered throughout the renal parenchyma (Figure 1B) peaking at 12 hours, consistent with previous findings by Liu et al 11 We then tested whether abrogating AT 1 receptor signals selectively within T lymphocytes influences the development of cisplatin-induced AKI. Wildtype (WT) mice and mice genetically deficient of the dominant murine AT 1 receptor isoform (AT 1A ) solely within T cells (TKO; Supplemental Figure 1) had similar levels of BUN and serum creatinine (sCr) after saline treatment, indicating that the T cell AT 1 receptor does not affect baseline renal function ( Figure 1, C and D).…”
supporting
confidence: 86%
“…Although our findings confirm the importance of CD4 + T lymphocytes in mediating cisplatin-induced AKI, 11 these experiments are the first, to our knowledge, to document a protective effect of the T cell AT 1 receptor in the setting of AKI and highlight a potential danger of treating patients who require cisplatin chemotherapy with an ARB. Although we cannot exclude a TNFindependent contribution to the exaggerated renal injury in the TKOs, the actions of AT 1 receptors on T cells to limit TNF production are consistent with our previous findings in the setting of hypertensive kidney damage and can accrue from both an effect on T-betmediated T cell differentiation and a reduction in T cell-renal tubular cell interactions caused by effects of the T cell AT 1 receptor on chemokine generation.…”
supporting
confidence: 55%
“…Compelling evidence suggests that renal dysfunction in different forms of AKI is the outcome of secretion of immune mediators [5][6][7][8][9] and the activation of renal resident and recruited leukocytes 2,3,10,11 ; however, recent studies also suggested that certain cytokines 40 -43 and immune cells 23,44,45 may limit kidney injury by reducing the immune-mediated inflammatory response. 46 During renal injury, DCs are thought to contribute to renal inflammation and exacerbate kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The elaborated chemokines and cytokines, including TNF-␣, IL-18, keratinocyte-derived chemokine, and monocyte chemoattractant protein 1, subsequently recruit additional immune cells to the kidney, such as neutrophils, T cells, monocytes, and inflammatory dendritic cells (DCs), which may cause further injury through pathways that are not fully defined. 2,[5][6][7][8][9][10][11][12] DCs are sentinels of the immune system and under steady-state conditions induce tolerance by various mechanisms, including production of TGF-␤, IL-10, or indoleamine 2,3-dioxygenase [13][14][15][16] ; expression of PDL-1, PDL-2, or Fc␥R2B 17,18 ; clonal deletion of autoreactive T cells 19 ; and induction of T regulatory cells via the inducible co-stimulator (ICOS) pathway. 20 -23 In response to pathogens or products of tissue injury, DCs mature and initiate immunity or inflammatory diseases.…”
mentioning
confidence: 99%
“…Splenocytes that were collected from WT mice were minced on a nylon mesh as described. 23 Approximately 5 Â 10 6 spleen cells were injected intraperitoneally into each IL-18Ra-deficient mouse 3 weeks before the IRI. IL-18Ra-deficient mice (n ¼ 5), WT mice (n ¼ 6), and IL-18Ra-deficient mice that received a transfer of splenocytes (n ¼ 8) were culled on day 1.…”
Section: Il-18ra and Acute Kidney Injury T Yano Et Almentioning
confidence: 99%